Following Jesus in the Modern World Between the Cross and the Selfie - Kalendonu, Lonny A; Tuela, Anita I.; Mawikere, Marde C. S. (International Journal of Education, Information Technology, and Others, 2025)
This title raises the tension between the call to discipleship, which demands self-denial and the willingness to take up the cross, and the reality of contemporary culture, which emphasizes self-image and popularity through social media. This article presents a theological-critical study on the meaning of discipleship in light of digital culture, which affects how individuals shape their identities, form communities, and understand spirituality. Using a qualitative reflective approach based on literature, this paper examines the literature on the theology of the cross, digital spirituality, and the phenomenon of modern narcissism in light of the Gospel. The author highlights how the selfie culture can harm the understanding of faith but also opens opportunities for contextual and creative spiritual reflection. The study's findings show that discipleship in the digital age requires the formation of an identity rooted in the cross of Christ, not in digital validation. This article encourages the church to establish an authentic, radical, and contextual pattern of discipleship in response to today's popular culture.